Design Approach of Tooth Profile Parameter for Harmonic Drive with Nice Meshing Performance - Dong Huimin; Zhang Jili (Jixie chuandong)
A tooth profile design approach for harmonic drive（ HD） with nice meshing qualities is proposed. The criteria for tip interference judge,interference zone determination and sample points generation,which will achieve the tooth profile design well are proposed in this method. When one HD tooth profile is given,tooth profile parameters of the other conjugate tooth are sufficiently determined by this method,which can remove tip interference but guarantee the meshing performance on the conjugate zone without repeated simulation,interference check and revise. Taking the design of a pair of tooth profiles of HD as example,the tooth profile parameter of rigid spline is designed under the given tooth profile of flexspline. Analysis of fitting error and backlash demonstrates that the designed tooth profile of the rigid spline is very close to the theoretical conjugate curve,the backlash distribution is ideal,the contact ratio and maximum engaging depth are guaranteed,which proves that the tooth profile parameter design method is effective and can guarantee the meshing performance.